SOEP-Core - 2021: Sampling, nonresponse, and weighting in wave 2 of living in Germany - Nationwide Corona-Monitoring (RKI-SOEP2) - Christian Danne; Maximilian Priem; Hans Walter Steinhauer (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
This paper describes the weighting methodology for the second wave of the Living in Germany - Nationwide Corona Monitoring study (RKI-SOEP2). Information from the larger, ongoing German Socio-Economic Panel (SOEP) study from which the households are sampled is used to analyze the determinants of non-contact, attrition, and refusal to participate at the household and individual level as well as to correct the data accordingly. For a sample of 6,791 households and 11,223 individuals, we find that personal attributes and socio-economic factors at the household level and the advent of the omicron variant are the key determinants at the household level for non-response. Demographic and socio-economic factors represent the most important predictors for non-response at the individual level.
Keywords: H12; I10; I18; C83; 330; Calibration; Weighting; Covid-19; SOEP; RKI; Lasso